In vivo Effects of Repeated Thyronamine Administration in Male C57BL/6J Mice. Issue 1 (5th January 2018) - Harder, Lisbeth; Schanze, Nancy; Sarsenbayeva, Assel; Kugel, Franziska; Köhrle, Josef; Schomburg, Lutz; Mittag, Jens; Hoefig, Carolin S.
Abstract : Objectives: Thyronamines are decarboxylated and deiodinated metabolites of thyroid hormones (THs). Of all possible thyronamine variants, only 3-iodothyronamine (3-T1 AM) and iodine-free thyronamine (T0 AM) have been detected in vivo. While intensive research has been done on the (patho-)physiological action of 3-T1 AM, the role of T0 AM has been studied less intensively. Study Design: We determined whether a single pharmacological dose (50 mg/kg, i.p.) or repeated administration (5 mg/kg/day, i.p., for 7 days) of T0 AM affects metabolism, cardiovascular function, or thermoregulation in male C57BL/6J mice. Since selenium (Se) is important for proper TH function and Se metabolism is affected by TH, we additionally analyzed Se concentrations in liver, serum, and kidney using total reflection X-ray analysis. Results: A single injection of T0 AM had no effect on heart rate, temperature, or activity as assessed by radio telemetry. Likewise, daily administration of T0 AM did not alter body weight, food or water intake, heart rate, blood pressure, brown adipose tissue thermogenesis, or body temperature, and no significant differences in hepatic glycogen content or mRNA expression of genes involved in cardiovascular function or metabolic control were determined. Also, the X-ray analysis of Se concentrations revealed no significant changes. However, hepatic T0 AM was significantly increased in the treated animals. Conclusions: In summary, our data demonstrate that T0 AM elicits no obvious metabolic, cardiovascular, or thermoregulatory activities in mice. As T0 AM does also not interfere with TH or Se metabolism, we conclude that the deiodination of 3-T1 AM to T0 AM constitutes an efficient inactivation mechanism, terminating the actions of the more powerful precursor.